Financial Profitability of Production and Marketing of Buffalo Milk in Lalitpur District, Nepal - K.C., C.; Panta, H.K. (Economic Journal of Development Issues, 2022)
Dairying is considered as a prestigious occupation among the agricultural sub-sectors in Lalitpur. The production of milk is concentrated in the peri urban and rural areas with the increase in demand for fresh milk in the urban areas. This study was conducted to analyse the economics of the production and marketing of buffalo milk in Lalitpur district, Nepal. This research was conducted from July 2021 to July 2022 collecting data from 123 respondents including farmers, collectors, key informants, and cooperatives working for milk related functions in Lalitpur district. The cost of rearing a milking buffalo was estimated NPR 5,762 per month, with the highest share of feed cost (47.8%) followed by labor cost (21.5%) and animal cost (13.1%). Results of Cobb-Douglas production function showed an increasing return to scale for milk production. Gross income, net income (per buffalo per month), and BCR were NPR 13,828, NPR 8,066, and 1.4, respectively. The cost of producing milk at the farmer’s level was far low than the National Dairy Development Board reported cost of production. The estimated mean technical efficiency was 92.41% for buffalo grower in a range of 88- 98%. Average monthly marketed surplus which was 92.7% of total production was around 3.05% less than the marketable surplus. Among the four milk marketing channels for buffalo milk supply, the longest channel i.e. Farmer-Collector-Large milk processors-Consumer has the highest price spread of 50.59% and producers’ share of 49.4%. The shortest channel i.e. Farmer – Collector –Consumer has the estimated price spread of 9.89% and producers’ share of 91.03%. Improving production and productivity is important in order to improve profit. The extension workers are suggested to make efforts and motivate farmers to acquire technical and management knowledge to increase dairy producers’ profits. Infrastructure development was below the standard for milking buffalo keeping and selling. Improving these weaknesses, study further suggest turning peri-urban regions of Lalitpur district as the primary milk production location within Kathmandu valley.